Streamlining Architectural Design Services with Mobile E-Commerce Development Using Integrated Payment Gateways - Galih Satrio Wicaksono; Afwan Anggara (Universitas Negeri Semarang, 2026)
Purpose: This research aims to design a mobile-based e-commerce system integrated with a payment gateway, as well as a centralized data management dashboard for A3+ Architect Design. The main focus of the research is on the efficiency of architectural design service business processes, including data management, information access, ordering mechanisms, payment integration, and real-time order monitoring for customers. Methods: The research methodology applied a systematic four-stage approach, including needs analysis to identify requirements through interviews with the A3+ studio, system model design, implementation, and testing. The system was built using client-server architecture with Flutter as the mobile application and Laravel as the web service and admin/designer dashboard. Functional validation of the system at the final stage was carried out using the black-box testing method. Result: Black box testing confirmed that all features are operating optimally and in accordance with the requirements specifications. The system successfully provides a comprehensive transaction workflow and an efficient operational dashboard for administrators and designers to support more organized data management. Novelty: The uniqueness of this research lies in the integration of a mobile application system with a web dashboard that is specifically tailored to the characteristics of the architectural services industry, which was previously dominated by manual processes. This research contributes to the digitization of customer services and increased transaction transparency, which directly impacts the strengthening of customer trust and the operational efficiency of service providers.